Respuesta :
Answer:
- 36[tex]w^{8}[/tex] - 36[tex]w^{6}[/tex] - 36[tex]w^{5}[/tex]
Step-by-step explanation:
Using the rule of exponents
[tex]a^{m}[/tex] × [tex]a^{n}[/tex] = [tex]a^{(m+n)}[/tex] , then
4[tex]w^{5}[/tex] (- 9w³ - 9w - 9) ← distribute parenthesis by 4[tex]w^{5}[/tex]
= - 36[tex]w^{(5+3)}[/tex] - 36[tex]w^{(5+1)}[/tex] - 36[tex]w^{5}[/tex]
= - 36[tex]w^{8}[/tex] - 36[tex]w^{6}[/tex] - 36[tex]w^{5}[/tex]
Answer:
[tex] = > 4 {w}^{5} ( - 9 {w}^{3} - 9w - 9) \\ \: \: \: \: = > - 36w {}^{5 + 3} - 36 {}^{5 + 1} - 36 {}^{5} \\ = > - 36 w{}^{8} - {36w}^{6} - 36w {}^{5} [/tex]